Efficacy of Trunk Barriers for the Control of Key Pests on Trellised Grapevines - Schwartz, A. (South African Journal of Enology and Viticulture, 2017)
Different trunk barriers were evaluated for the simultaneous control of snoutbeetles (Phlyctinus ca/losus Bob., Eremnus setulosus Bob.) and the Argentine ant lridomyrmex humi/is (Mayr.) on trellised grapevines. The polybutenebased sticky barriers Fo1·mex, Formex on Bidim and Plantex were effective in preventing snoutbeetles and ants from gaining access to the vegetative part of the vine. Phytotoxicity did not occur.